PENENTUAN pH OPTIMUM ISOLASI KARAGINAN DARI RUMPUT LAUT JENIS Eucheuma cottonii - I G. A. G. Bawa; A. A. Bawa Putra; Ida Ratu Laila (Jurnal Kimia (Journal of Chemistry), 2007)
This research aimed to determine the optimum pH for the isolation carrageenan from Eucheuma cottoniiseaweed. The isolation was conducted at various pH : 7.5, 8.0, 8.5, and 9.0. A TLC using methanol : water (5:1) asmobile phase from standard carrageenan, gave result on Rf value 0.74 as equal to sample on treatment condition atpH 8.0 and 8.5. whereas, sample on treatment condition at pH 7.5 and 9.0 gave Rf value 0.72. In using ethanol :water (3:1) as mobile phase gave result on Rf value 0.75 from both standard and sample treated at 7.5, 8.0, and 8.5,while at pH 9.0 gave Rf value 0.74. Melting point test from standard gave range value 240-242, while for sample ontreatment condition at pH 7.5, 8.0, 8.5, and 9.0 gave range value each such 242-244, 241-243, 240-242, and 240-243.Compounds identification with solubility test method using various solvent medium obviously showed that both ofstandard and sample from various treatment condition were insoluble such as in aquades 200C, NaCl 25% 200C and800C, saccharosse 65% 200C and chloroform. Otherwise, they were soluble in aquades and saccharosse 65% withtemperature 800C. Infrared spectrum standard compound and sample from various treatment condition indicatedthat they were identical. Carrageenan isolation produce the largest number of rendemen at pH 8.5 with about34.65%, while the variant of carrageenan isolate was classified by kappa carrageenan.